2018
DOI: 10.26434/chemrxiv.6304460
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Achilles' heel of Iron-Based Catalysts During Oxygen Reduction in Acidic Medium

Abstract: Fuel cells efficiently convert chemical into electric energy, with promising application for clean transportation. In proton-exchange membrane fuel cells (PEMFCs), rare platinum metal catalyzes today the oxygen reduction reaction (ORR) while iron(cobalt)-nitrogen-carbon materials (Fe(Co)-N-C) are a promising alternative. Their active sites can be classified as atomically dispersed metal-ions coordinated to nitrogen atoms (MeNxCy moieties) or nitrogen functionalities (possibly influenced by sub-surface metallic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 0 publications
2
32
0
Order By: Relevance
“…A similar deactivation is also observed for pyrrolic complexes and is well-documented in the literature [148][149][150]. These observations highlight the important role of the carbon framework in increasing the relative stability of Fe-N4 sites in Fe-N-C materials against oxidative and protolytic decomposition induced by the acidic conditions and the presence of parasitic amounts of H2O2 151. Indeed, we posit that extending the aromatic periphery around the (phen2N2)FeCl active site could enhance stability and provide a path towards the bottom-up synthesis of robust Fe-based ORR catalysts.CONCLUSIONSThe results reported herein provide a molecular perspective on the structure and oxygen reduction reactivity of Fe-N4 active sites in Fe-N-C materials.…”
supporting
confidence: 86%
“…A similar deactivation is also observed for pyrrolic complexes and is well-documented in the literature [148][149][150]. These observations highlight the important role of the carbon framework in increasing the relative stability of Fe-N4 sites in Fe-N-C materials against oxidative and protolytic decomposition induced by the acidic conditions and the presence of parasitic amounts of H2O2 151. Indeed, we posit that extending the aromatic periphery around the (phen2N2)FeCl active site could enhance stability and provide a path towards the bottom-up synthesis of robust Fe-based ORR catalysts.CONCLUSIONSThe results reported herein provide a molecular perspective on the structure and oxygen reduction reactivity of Fe-N4 active sites in Fe-N-C materials.…”
supporting
confidence: 86%
“…Previous researchers have found that the Fe-N-C catalyst has a stable structure but unstable electrochemical performance when exposed to H 2 O 2 (ORR by-product) in acidic electrolyte [ 49 ]. The catalytic active site of the Fe-N-C catalyst was not be affected, but its conversion frequency was reduced through the oxidation of the carbon surface, resulting in the weakening of the binding ability of the Fe-N-C catalyst to O 2 .…”
Section: Resultsmentioning
confidence: 99%
“…This hypothesis is in line with our recent work that demonstrated decreased TOF of Fe-based sites by chemical reaction of Fe0.5 with H2O2. 25 The activity drop from 0 to 5 h of operation is thus assigned to both decreased TOF via mild surface oxidation of carbon (vertical arrows in Figure 5e), and decreased number of S1 sites (arrows along the dashed lines in Figure 5e). After 5 h operation, the TOF of the Fe sites seems stabilized, leading to linear correlations between the overall activity and either D1 or D1+D2.…”
Section: Fementioning
confidence: 99%